In-service science teachers' purposes for integrating the history of science: the role of their science teaching orientation - ÇAKIR, MUSTAFA (My University, 2022)
This qualitative study examined teachers\" science teaching orientations (STO) and their purposes for integrating the history of science (HOS) into their teaching using newly developed instructional materials. The HOS may be used as an effective instructional tool for achieving scientific literacy; however, science teachers utilise it in various ways for very different purposes. Data was collected from nine in-service high school science teachers using an orientation interview protocol, reflective journals and semi-structured interviews. Data collection focused on the experiences of participating teachers who implemented instructional materials based on HOS over the course of two years. Participants\" STO profiles were classified into three groups: traditional, transitional and reformist. Data analysis revealed 13 distinct purposes for integrating HOS, which fell under four overarching domains: namely, pedagogical, conceptual, affective and epistemological. The results of the study revealed that teachers failed to relate HOS with the tenets of nature of science (NOS) in their teaching. They were not able to identify the potential NOS aspects within the HOS materials. Only the reformist teachers integrated HOS for epistemological purposes, whereas the traditional teachers relied on HOS simply as an interesting life and work stories of well-known scientists. Teachers could use HOS instructional materials for a variety of reasons by utilising different aspects of HOS as their views on science and teaching shift from traditional to reformist.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); General Social Sciences; Social Sciences & Humanities; History of science; science teachers; science teaching orientation; using the history of science; EPISTEMOLOGICAL BELIEFS; SCHOOL SCIENCE; KNOWLEDGE; PHILOSOPHY; STUDENTS; ATTITUDES; EDUCATION; PHYSICS